ECONOMY VARIABILITY IN A PANDEMIC: FINANCIAL AND ECONOMIC IMPACTS FOR COUNTRIES AND TERRITORIAL COMMUNITIES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The new challenges posed by the effects of the COVID 19 pandemic have exacerbated a number of risks to the continued functioning and sustainable progress of both local communities and the country as a whole. The pandemic, combined with the Government's measures to contain and spread the virus, had a negative impact on the country's economy and local communities. In this context, the need to assess existing and potential challenges and threats to the economic and social development of the country and communities was raised.The purpose of the article is to analyze the financial and economic consequences of the pandemic for the sustainable progress of both communities and Ukraine and to justify anti-crisis measures aimed at overcoming the challenges.The methodology of scientific research of economic variability in a pandemic and its impact on the economic and social development of territorial communities and the country is based on the use of the principles of a systematic approach, structural analysis and generalization.The peculiarities of the functioning of the economy in a pandemic in Ukraine in terms of key activities are revealed. Financial and economic challenges are analyzed, emphasis is placed on potential threats. Problematic aspects have been identified both in the economic sectors and in state and local finances. It is proved that dynamic changes in all spheres of activity require instant appropriate strategic and tactical decisions. In order to minimize the impact of the pandemic on the sustainable development of the country and communities, a number of short- and medium-term initiatives have been proposed: government support for the most vulnerable sectors of the economy (including tax holidays; moratorium on business inspections; 0% SSC for entrepreneurs working in the most affected) »Industries); financial support for vulnerable groups; compensation for losses of local budget revenues (renewal of Article 103 of the Budget Code of Ukraine).
Keywords: uncertainty, pandemic, crisis, financial and economic challenges, economic variability.